Serious Applications in a First-Person Shooter Style Game in Virtual Reality - Gonçalves, Thiago da Silva; Almeida, Raphael de Souza e; Porcino, Thiago Malheiros; Raposo, Alberto Barbosa (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais Estendidos do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Armed conflicts have become increasingly common in urban environments, often occurring in confined spaces with the presence of many people. In such situations, it is imperative that military personnel are prepared for this reality, where mistakes can cost lives. This study examined the use of Virtual Reality as a support tool in decision-making during Close Quarters Combat. Two virtual environments were used: one for training and another to verify target identification. The study found positive results, which support the use of virtual reality for this purpose.